1998
DOI: 10.2514/2.4202
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Hover-to-Forward-Flight Transitions for a Thrust-Vectored Aircraft

Abstract: The use of differential atness for computation of a nominal trajectory for fast transition between ight modes of autonomous vehicles is investigated. Differential atness of an approximate model of the longitudinal dynamics of a thrust-vectored aircraft is used to achieve fast switching between ight modes. We conclude that steering to the trimmed state of the full model is of crucial importance for good performance. Simulations and experimental data for a thrust-vectored ight-control experiment at Caltech are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…, u (p) ) such that all feasible solutions of the underdetermined differential equation (1) can be written as Differentially flat systems were originally studied by Fliess et al [9]. See [24] for a description of the role of flatness in control of mechanical systems and [33] for more information on flatness applied to flight control systems.…”
Section: Differential Flatness and Trajectory Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…, u (p) ) such that all feasible solutions of the underdetermined differential equation (1) can be written as Differentially flat systems were originally studied by Fliess et al [9]. See [24] for a description of the role of flatness in control of mechanical systems and [33] for more information on flatness applied to flight control systems.…”
Section: Differential Flatness and Trajectory Generationmentioning
confidence: 99%
“…In this way, we reduce the problem of generating a feasible trajectory for the system to a classical algebraic problem in interpolation. Similarly, problems in trajectory generation can also be converted to problems involving curves z(·) and algebraic methods can be used to provide real-time solutions [33,34].…”
Section: Example 1 (Planar Ducted Fan)mentioning
confidence: 99%
“…In Primbs et al [26], aspects of a stability-guaranteeing, global control Lyapunov function were used, via state and control constraints, to develop a stabilizing receding horizon scheme. Many of the nice characteristics of the CLF controller together with better cost performance were realized.…”
mentioning
confidence: 99%
“…The seminal work for the transition phenomena on UAV platforms can be attributed to Nieuwstadt and Murray [5]. During the study [14] In recent studies, Green and Oh [22][23][24] The utilization of flaps and slats is shown to improve the transition performance by reducing altitude gain but with penalty on the transition time During the wind-tunnel testing by Moschetta et.…”
Section: Related Workmentioning
confidence: 99%
“…The aerodynamic properties discussed up to this point are steady or quasisteady in nature and has been used for evaluating agile maneuvers in most investigations [5,29,33,43]. In a quasi-steady approach, any change in angle of attack of the aircraft results in instantaneous change in aerodynamic properties.…”
Section: Unsteady Aerodynamic Estimationmentioning
confidence: 99%